Decision-Making Within Forensic Psychiatric Investigations: The Use of Various Information Sources by Different Expert Groups to Reach Conclusions on Legal Insanity - Göranson, Lizel; Svensson, Olof; Andiné, Peter; Bromander, Sara; Bagge, Ann-Sophie Lindqvist; Karlén, Malin Hildebrand (Frontiers in Psychiatry, 2022)
Which types of information experts use to make decisions regarding legal insanity within Forensic Psychiatric Investigations (FPI) is relatively unknown, both in general and when considering variations due to case-context. This area is important to explore to be able to counteract the effects of various kinds of cognitive bias. Method. The aim was to explore whether FPI-expert groups differed regarding case-specific as well as general use of information types required to make decisions on severe mental disorder (SMD). Three FPI case vignettes were presented to three professional groups involved in FPIs in Sweden (n=41): forensic psychiatrists (n=15), psychologists (n=15), social workers (n=11). Participants reported which types of information they required to reach conclusions regarding SMD in each case. Also, they reported which types of information they had used within general FPI praxis during the previous year, and the information types’ perceived usefulness. Results. Expert groups differed somewhat regarding what type of information they required for the cases (e.g. results from cognitive testing), but some information was required in all cases (e.g. client’s self-report). Regarding the preliminary assessment of SMD in the three cases, minor differences were found. Within general FPI praxis, experts reported using several information types, while the general perceived usefulness of these sources varied. Discussion. The professional groups relied partly on a ‘core’ of information sources, but some case-specific adaptations were found. Professional groups’ inclination to suspect SMD also varied somewhat. This indicate need for exploring potential consequences of these similarities and differences.